The Principal Entrepreneurial Competence and Teachers' Role Influence on the Green-Clean-Creative School Program Success at State Elementary Schools in Kebayoran Lama Sub-district - Aprilia Wahyu Ramadhani; Udan Kusmawan; Ajat Sudrajat (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Principals and teachers have a role and a close relationship in achieving the success of program in schools. In this case, the principals' entrepreneurial competence and the teachers' role have a major role in the success of the school programs. This study aimed to obtain information about the principal entrepreneurial competence influence, the teacher's role influence, and the principal entrepreneurial competence and the teacher's role influence on the success of the “Green-Clean-Creative School” program. This research was conducted at public elementary schools in the Kebayoran Lama Sub-district. The method used was quantitative research. The data collection techniques were a questionnaire method, observation sheets, and documentation. The research samples were 11 principals of public elementary schools and 55 teachers of public elementary schools in the Kebayoran Lama Sub-district. The data analysis method in this study employed Pearson Product Moment correlation test on validity test, Alpha Cronbach test on reliability test, and Spearman Rank correlation test on hypothesis testing. The results found a significant influence between the principal's entrepreneurial competence and the teacher's role in the success of the Green-Clean-Creative School program because the F-count was 57.352 which was greater than the F-table (4.26). The test results also showed that the significance value of the F-test was 0.000 which was smaller than the specified probability α, i.e., 0.000 0.05. Thus, it can be synthesized that the principal's entrepreneurial competence and the teacher's role had a significant effect on the Green-Clean-Creative program success at state elementary schools in the Kebayoran Lama Sub-district.